Dampak Pembelajaran Berbasis Masalah (PBL) Terintegrasi Canva dan PHeT Terhadap Keterampilan Pemecahan Masalah Siswa pada Materi Gerak Dan Gaya - Alif Muhammad Hafiz Ihsan; Sabar Nurohman; Ismail Fikri Natadiwijaya (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to analyze the effect of Problem-Based Learning (PBL) assisted by Canva and PhET media on students’ problem-solving skills in science learning. The method used was a pre-experimental design with a one-group pretest-posttest approach on motion and force topics. The participants were 32 seventh-grade students of SMPN 11 Yogyakarta. Data were collected using pretest and posttest instruments designed to measure students’ problem-solving skills. The results showed an improvement in students’ problem-solving skills after the implementation of PBL assisted by Canva and PhET. The mean score increased from 40.47 in the pretest to 76.95 in the posttest. Normality test results indicated that the pretest (0.598) and posttest (0.881) data were normally distributed, as the significance  values  were  higher  than  0.05.  The  paired  sample t-test showed a significance value of 0.000 (p < 0.05), indicating a significant difference between pretest and posttest scores. The N-Gain analysis yielded a value of 0.62, which is categorized as moderate. The conclusion of this study is that the integration of PBL with Canva and PhET interactive media is effective in improving students’ problem-solving skills in science learning. Keywords: Canva, PhET, Problem-Based Learning, Problem-Solving Skills, Science Learning.